Determination of Recipients of Livestock Assistance for Villages Using the Simple Additive Weighting Method - Anisyah Juniarti; Siswanto Siswanto; Jhoanne Fredricka (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2023)
Decision support systems are systems capable of providing data and information. In today's digital and globalization era, where the need for fast, precise and accurate information is very important. What's more, currently various public and private agencies will develop their businesses, one of which is to make changes by utilizing sophisticated technology such as computers as a substitute for human labor, The simple additive weighting method is one of the methods used to solve the problem of fuzzy multiple attribute decision making (FMADM). The simple additive weighting (SAW) method is a method used to find optimal alternatives from a number of alternatives with certain criteria. The result of this research is a software that adopts the SAW method which is able to assist the agriculture and animal husbandry department for decision making in determining recipients of livestock assistance every year.